The year of second chances : [large type] a novel - Avery, Lara (Thorndike Press large print dynamic drama, 2023)
"In this dazzling debut, Lara Avery crafts a story of heart, humor, and hope, as a young widow learns that her late husband signed her up for a dating service before his death, propelling her on an uplifting journey of possibility, second chances, and falling in love again...with life. Robin Lindstrom spent her first year as a young widow cocooned in the safe haven of the Minnesota farmhouse she'd once shared with Gabe, the love of her life - the man she thought she'd be with 'til the end. But her world is turned upside down when she receives an email informing her that her late husband has enrolled in something called "Fluttr" - a dating service? The app subscription lasts 12 months; use it!, Gabe's message-from-the-grave reads. I don't like the thought of you being alone. If you won't do it for yourself, do it as a favor to me. Please. After twelve months of pulling herself together, Robin's fragile equilibrium is knocked sideways. How could Gabe, of all people, be asking her to venture out into the murky waters of 21st century online dating? As her underemployed brother, Theo, points out, it's "only" a year, and it's what Gabe wanted; he set this all up to go into effect a year after his death, which means it was basically his last request. And so Robin tentatively takes steps to put herself out into the world once more, even if it means awkward outings at bowling alleys, club-hopping with DJs she meets online, and stammering conversations at dinner. Along the way, she's surprised to find herself meeting new people, trying new things...and even getting to know a new version of herself. Because everyone deserves a second chance at love--and loving life"--